Pendampingan Peran Keluarga terhadap Tumbuh Kembang Anak pada Masa Pandemi Covid-19 Di RA Al Hilal Pamolokan - Emdat Suprayitno; Zakiyah Yasin (Jurnal Empathy Pengabdian Kepada Masyarakat, 2021)
Background: The main environment for children is the family. The child's personality can be supported through the main role of the family. the family also has a role in monitoring and providing supervision of children's growth and development, so that if this role is inadequate then the child's growth and development will not be monitored properly and disturbances that can occur cannot be identified and overcome early on. COVID-19, of course, requires the role of the family to fulfill health needs, fulfill adequate nutrition, and provide proper care. Methods: The assistance provided by the researcher is providing counseling and practice on evaluating the stimulation practices that have been carried out, providing feedbacks, and teaching stimulation practices for those aged above. Stimulation of Early Intervention Detection of Child Development is an activity to stimulate the basic abilities of children aged 0-6 years so that children grow and develop optimally, as well as to find deviations early to make intervention easier. Results: Through PKM activities, children's growth and development, the worst conditions of child growth deviations such as malnutrition can be prevented, because before a child falls into a condition of malnutrition, growth deviations that occur in children can be detected through PKM activities. Conclusion: Addition to preventing growth irregularities, this activity also prevents developmental deviations and mental-emotional deviations during the Covid-19 pandemic.